Handbook of Communication and Aging Research. - Nussbaum, Jon F. (Communication., 2004)
This work shows that aging is not only an individual process but an interactive one. The study of communication can lead to an understanding of what it means to grow old. Many of the chapters work to deny earlier images of aging as involving normative decrement to provide a different view of aging.